Discussion on the influence of nanoparticle characteristics in New Coronavirus Disease-19 and severe acute respiratory syndrome Coronavirus 2 - Shenguo Wang (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2021)
In the paper, why New Coronavirus Disease-19 (COVID-19) should belong to a class of protein nanoparticle and possessed ultra-small size and super-penetration capability, as well as effect of the COVID-19 characteristic on follows phenomena were discussed. (1) The difference existed on toxicity, transmission speed and diffusion range of the COVID-19 and Severe acute respiratory syndrome (Sars) virus. (2) The different time interval between COVID-19 infection and discover existed in different person. (3) The different time interval in "new crown virus infection", "asymptomatic infection", "suspected case" and "re-infection" produced existed in different person. (4) The different time interval from COVID-19 infection to produce SARS‑CoV‑2 disease existed in different person. The improve methods and suggestion for avoiding and preventing COVID-19 infection and treating SARS‑CoV‑2 were proposed.